Moralisk exkludering - om tiggare i medier i Norr- och Västerbotten - Nilsson, Bo (Socialvetenskaplig tidskrift, 2016)
Morality and exclusion – media representations of beggars in the north of Sweden Many public poor from Romania and Bulgaria arrived in the northern parts of Sweden in 2013 and especially in 2014, and a majority of them supported themselves by begging. The media described this new phenomenon in various ways, for example by reporting on how people (Swedes) were outraged because of all the beggars in public spaces. Others, however, described it as if the north of Sweden (finally) had become a part of the rest of the world. This paper discusses how newspapers in Norrbotten and Västerbotten (two large provinces in the north of Sweden) reported on beggars in 2013 and 2014. The overall aim is to qualitatively describe and analyse how the media reported on the beggars, and to discuss the media representations in terms of social inclusion and social exclusion as well as the meanings of morality. This means that the paper examines how journalists and other writers position beggars in relation to a majority population. The aim is also to investigate how journalists and other writers position themselves as moral subjects when they report on this vulnerable group of people. The study identifies four overarching discourses of beggars, and all of these are characterized by social exclusion of beggars even though the writers show inclusive ambitions on moral grounds. One reason for this is found in a subject-object logic that represents an organizing meaning-making principle in all discourses and that results in a categorization of people into “us” versus “them”, with the beggars representing the latter.